PkM Ginger Cultivation in Betao Village, Sidrap Regency: PkM Budidaya Jahe Desa Betao Kabupaten Sidrap - Amalia Zul Hilmi; Asmeati Asmeati; Andi Febriana Tamrin (Mattawang: Jurnal Pengabdian Masyarakat, 2023)
Betao Village, Pituriawa District, Sidrap Regency is an area that has a diversity of regional special drinks, one of which is instant ginger (sarabba). The PKM team aims to train (a) Making Appropriate Technology (TTG) in the form of sarabba "Penyerbuk" tools; (b) Training on ginger cultivation (c) Training on making sarabba powder packaging and (d) Mentoring by utilizing ginger. The method that will be applied is the introduction of making and training on the operation of the "Penyerbuk" tool, demonstration and how to make ready-to-eat sarabba in powder form, counseling on ginger cultivation, and marketing methods for sarabba powder products and business management training. The outputs of this PKM activity are (a) Appropriate technology tools in the form of sarabba "Penyerbuk" tools; (b) Ginger cultivation counseling (c) Sarabba powder products that still have the distinctive taste of Sidrap Regency. Abstrak Desa Betao Kecamatan Pituriawa Kabupaten Sidrap adalah daerah yang memiliki keanearagaman minuman khas daerah salah satunya adalah jahe instan (sarabba). Tim PKM memiliki tujuan untuk melatih (a) Pembuatan Teknologi Tepat Guna (TTG) Berupa alat “penyerbuk” sarabba; (b) Pelatihan mengenai budidaya jahe (c) Pelatihan pembuatan kemasan sarabba bubuk dan (d) Pendampingan dengan memanfaatkan jahe. Metode yang akan diterapkan adalah introduksi pembuatan dan pelatihan pengoperasian alat “penyerbuk”, demonstrasi dan cara pembuatan sarabba yang siap saji dalam bentuk serbuk, penyuluhan budidaya jahe, dan metode pemasaran produk sarabba bubuk dan pelatihan manajemen usaha. Luaran dari kegiatan PKM ini adalah (a) Alat Teknologi tepat guna berupa alat “penyerbuk” sarabba; (b) Penyuluhan budidaya jahe (c) Produk Sarabba bubuk yang tetap memiliki cita rasa khas Kabupaten Sidrap.